The Influence of the Amount of Raw Materials and Labor on the Level of Industrial Income at UD Setya Abadi D.M - YULIANI, Handita Rizki; HARIYANA, Nanik (Integration: Journal Of Social Sciences And Culture, 2024)
Purpose: The main goal of establishing a company is to produce far more than its operational costs. With profit growth, or what we often refer to as profit, it is hoped that it can finance the company's operational activities sustainably. This research aims to determine the effect of raw materials and labor on the level of industrial Income at UD. Setya Abadi D.M. Methodology: The analytical method used is quantitative. This study used a documentation study approach, using firm financial reports from the previous three years to gather data. Findings: The research results show that the level of raw materials has a positive and significant influence on industrial Income at UD. Setya Abadi D.M. As raw materials become available, industrial Income will also increase. Labor has a negative and significant influence on industrial Income at UD. Setya Abadi D.M. This means that when the number of workers increases, it does not affect the level of industrial Income. Implication: Furthermore, raw materials and labor together positively and significantly influence the level of industrial Income at UD. Setya Abadi D.M., the industry's income level will increase when both become more efficient.